Diseño urbano-arquitectónico de la franja periférica. Zona 5: turística-ciudad Francisco de Orellana (Coca) - Velástegui Toro, María Belén (2016)
The proposal made in the ARO-960 Workshop, expect to change the city Francisco de Orellana into a regional tourism network system. That links the urban area with the nature that surrounds it, given its location between three rivers. It will turn the city into a polycentric and compact one, seeking to potentiate existing centralities. Therefore, were established three zones along the city in order to have a variety of uses and facilities. Over the banks of the rivers Payamino, Napo and Coca, which borders the city, it is proposed to keep 100m for a buffer zone, as public space used for different recreational activities, leisure and basic equipment for a proper operation. The eastern area of the Coca River, suffers from severe flooding, endangering the urban area, therefore the proposal of a flooded park is essential within the development vision of the city, as a way to protect the area and increase the tourism. The urban architectural - design of the buffer zone, arises from the need to protect the citizens against floods. Nowadays, the area has been inhabited with buildings that are not suited for the increase of the river levels. Hence it is proposed to develop a sustainable public space to mitigate the flood and design areas for recreation, leisure, lookouts, and paths that connect the city with the park and the Coca river; at the same time, it will provide functionality to the project regardless if the water level is high or low. The flooded park covers a variety of equipment for different purposes, it develops projects of the Museographic Exhibition Center that seeks to merge and reflect the natural phenomena of the environment within each pavilion providing new sensations, followed by the tower – viewing platform, that besides supporting the drinking water, it proposes a number of high platforms that can generate up several viewpoints towards the city, the rivers and the park itself also collects water drops from the condensation of moisture, this way an urban self-sustainable architectural project that benefits the city and connectivity with the natural environment, is built.